Contraceptive Need, Intimate Partner Violence, and Reproductive Coercion Among Women Attending a Syringe Exchange Program. Issue 4 (July 2020) - Perry, Rachel; Landrian, Amanda; McQuade, Miriam; Thiel de Bocanegra, Heike
Abstract : Objective: Women who use drugs are at high risk of unintended pregnancy. This study describes contraceptive need, explores relationships between contraceptive use, intimate partner violence (IPV) and reproductive coercion, and unintended pregnancy, and assesses the acceptability of receiving contraceptive care at a syringe exchange program (SEP). Methods: Between August and October, 2017, written surveys were administered to 96 reproductive-aged women attending an SEP in Santa Ana, California. Data were analyzed using descriptive, bivariate, and multivariate statistics. Results: Most women used methamphetamines (79%) and/or heroin (74%). The majority (62%) did not use contraception during last sex with a man. Half (50%) reported a history of unintended pregnancy. Many (62%) experienced IPV or reproductive coercion in the previous 3 months. Experiencing IPV or reproductive coercion was not associated with contraceptive use or unintended pregnancy. The majority (56%) were interested in receiving contraceptive care from the SEP; history of unintended pregnancy (adjusted odds ratio [aOR] 3.5, 95% confidence interval [CI] 1.3–10.0) and depression (aOR 4.55, 95% CI 1.24–16.69) were associated with interest in contraceptive services. Conclusions: Our findings suggest that referrals for contraceptive care and direct provision of contraceptive methods at SEPs may be an acceptable approach to addressing the unmet family planning needs of women who use substances. Innovative approaches like these have the potential to impact the high prevalence of unintended pregnancy among this population; however, high prevalence of IPV and reproductive coercion must also be acknowledged by providers when providing counseling for contraceptive services.